1983
DOI: 10.1111/j.1471-0528.1983.tb08946.x
|View full text |Cite
|
Sign up to set email alerts
|

Tubal mucosa and ectopic pregnancy

Abstract: Summary. Fallopian tubes containing a gestation are frequently normal on macroscopical and gross histological examination. Scanning electron microscopy and light microscopy studies of tubal biopsies taken from five groups of women showed marked differences in the ciliated surface which was measured planimetrically on photographs. The proportion of ciliated cells was significantly lower in biopsies taken from 25 women with tubal pregnancies compared with that in biopsies from seven women with intrauterine preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 10 publications
0
22
1
3
Order By: Relevance
“…This finding is similar to reports from previous authors. [4][5][6][7][8][9][10][11][12][13] The reason for this might be explained by the findings of an earlier study, [21] which revealed that all the biopsies from patients with ectopic pregnancies or a history of ectopic pregnancy showed a marked degree of deciliation. It was further explained that loss of ciliated cells from the ampulla may decrease the efficiency of ovum transport, leading to delay in the ovum entering the isthmus and subsequently the uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to reports from previous authors. [4][5][6][7][8][9][10][11][12][13] The reason for this might be explained by the findings of an earlier study, [21] which revealed that all the biopsies from patients with ectopic pregnancies or a history of ectopic pregnancy showed a marked degree of deciliation. It was further explained that loss of ciliated cells from the ampulla may decrease the efficiency of ovum transport, leading to delay in the ovum entering the isthmus and subsequently the uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pregnancy commonly occurs in the fallopian tubes (97%). 8 Although women with ectopic pregnancy frequently have no identifiable risk factors, a prospective and case controlled study has shown that increase awareness of ectopic pregnancy and knowledge of the associated risk factors like pelvic inflammatory disease, history of previous ectopic pregnancy, tubal sterilization and any previous pelvic or abdominal surgery help in identifying women at higher risk in order to facilitate early and more accurate diagnosis. 9 Management of the case depends on the clinical presentation, site of the ectopic and need for future reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions causing dysregulation of these signals, such as tubal damage resulting from infection (8)(9)(10), are thought to alter tubal transport and the tubal microenvironment, inducing a receptive phenotype in the FT and predisposing to ectopic pregnancy (2,3). FTs from women with ectopic pregnancy contain less ciliated epithelial cells (2,11).…”
mentioning
confidence: 99%